Pelatihan Pemanfaatan Sistem Informasi Geografis bagi Pengelola Hutan Kemasyarakatan Hinje Simpei di Kabupaten Pulang Pisau Kalimantan Tengah - Iskandar, Beni; Purnama, Ardiyansyah; Putro, Dhymas Sulistyono (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service activity aims to enhance the capacity of the Hinje Simpei Forest Farmer Group (KTH) in managing Community Forests (HKm) through the application of Geographic Information System (GIS) technology to support inventory, spatial management planning, and sustainable monitoring of biophysical conditions. The implementation methods include four stages: socialization, training, technology application, and mentoring. The evaluation instruments employed a quantitative analysis using a pre-test and post-test design, followed by a paired t-test to identify significant differences. The results of this community service activity indicate an improvement in the capacity of the Hinje Simpei Forest Farmer Group in utilizing GIS for inventory, spatial planning, and biophysical monitoring. The strengths of this program include the use of a participatory approach, enhanced technical skills through hands-on practice, and the development of thematic maps that serve as valuable references for forest management. This program provided new insights and strengthened GIS-based management practices for the Hinje Simpei Community Forest.